Dynamics of marine sands a manual for practical applications - Soulsby, Richard (Thomas Telford, 1997)
This work summarises the main processes determining the behaviour of sand in the sea. The results are intended to provide the tools with which the practising engineer can make calculations of sand behaviour as it affects engineering works.